THE INFLUENCE OF LIGHT QUALITY IN THE in vitro CULTIVATION OF Cattleya crispata Van den Berg (Nativa, 2021)
ABSTRACT: Micropropagation technique is a valuable alternative for high quality genetic preservation of endemic species such as the orchid Cattleya crispata from “Campo Rupestre Ferruginoso”. This study aims to evaluate the influence of light quality on in vitro multiplication and elongation phases, offering new insights on the limiting factors of C. crispata. Seeds extracted from capsules were used for inoculation in the culture medium. Four light sources were evaluated for in vitro culture, namely: fluorescent lamp, white LEDs, red LEDs and red/blue LEDs. Data about the number of shoots, shoot length, shooting vigor and pigment content were assessed at 90 days of in vitro culture. Based on the recorded results, white LEDs are the most suitable ones for in vitro multiplication and elongation phases of C. crispata. It offers higher quality for seedling production and increases the chances of genetic conservation of the species.Keywords: ‘Campo Rupestre Ferruginoso’; in vitro propagation; wavelength; LEDs. A qualidade da luminosidade influencia o cultivo in vitro de Cattleya crispata (Thunb.) Van den Berg RESUMO: A micropropagação é uma alternativa para a conservação genética de espécies endêmicas do Campo Rupestre Ferruginoso, como a orquídea Cattleya crispata, tendo vantagem a maximização da propagação em elevada qualidade. Para solucionar os fatores limitantes ao cultivo in vitro de C. crispata, o presente trabalho teve como objetivo avaliar a influência da qualidade de luz nas fases de multiplicação e alongamento in vitro. Sementes extraídas de cápsulas foram utilizadas para a inoculação em meio de cultura. Avaliaram-se quatro fontes de luz (Lâmpada fluorescente, LEDs branco, LEDs vermelho e LEDs vermelho/azul). Dados referentes ao número, comprimento de brotos, vigor das brotações e conteúdo de pigmentos foram avaliados aos 90 dias de cultivo. Com base nos resultados obtidos, pode-se inferir que LEDs branco é mais adequada para ser utilizada nas fases de multiplicação e alongamento in vitro de C. crispata, sendo uma alternativa para a produção de mudas e conservação genética.Palavras-chave: Campo Rupestre Ferruginoso; propagação in vitro; comprimento de onda; LEDs.